Mastoid cavity obliteration in CWD mastoidectomy with periosteal-pericranial flap: A 10-year experience - Tawalbeh, Mohammed; Al-rawashdeh, Baeth; Ali, Elnagi; Alzarea, Abdulaziz; Alzarea, Abdullah; Alsharari, Abdulaziz; Alsharari, Bader; Elkhatib, Ahmad (Jordan Medical Journal, 2021)
Aim: To present our ten-year experience in mastoid obliteration using the inferiorly based postauricular periosteal-pericranial flap in canal wall down (CWD) tympanomastoidectomy, and review its efficacy in producing a dry, small, low-maintenance mastoid cavity. Materials and methods: A retrospective study of sixty-four consecutive procedures of CWD tympanomastoidectomy was conducted over the period from 2007 to 2017 for the treatment of active chronic otitis media, with or without cholesteatoma. The main outcome measure was the successful control of suppuration to create a dry, self-cleansing mastoid cavity. Results: Fifty-three ears (82.8 %) had a small, dry, healthy, and self-cleaning mastoid cavity. Four ears (6.3%) had intermittent otorrhea easily controlled by topical and systemic antibiotic treatment and aural toileting. Seven patients (10.9 %) had persistent otorrhea of which three had meatal stenosis, two had granulation tissue and two had recurrence of cholesteatoma. Outcomes remained stable over progressively more extended follow-up periods (up to 132 months). Conclusion: The use of postauricular periosteal-pericranial flap for mastoid obliteration in CWD tympanomastoidectomy is a very effective technique that results in a dry, small, self-cleaning mastoid cavity in 89.1 % of patients with active chronic otitis media with or without cholesteatoma.